The effect of school well-being on grit with growth mindset as a mediator for students of SMK Harapan Bangsa Tanjung Morawa - Siagian, Iqbal Warid; Hasanuddin, Hasanuddin; Dewi, Salamiah Sari (Science Midwifery, 2025)
Students of Sekolah Menengah Kejuruan (vocational high schools) are required to possess grit in facing various challenges, such as career preparation and industrial internships. However, in reality, some students experience decreased enthusiasm, career uncertainty, and a tendency to give up easily when dealing with academic pressures. This study aims to examine the effect of school well-being on grit with growth mindset as a mediating variable among students of Sekolah Menengah Kejuruan Harapan Bangsa. This research employed a quantitative approach using Structural Equation Modeling (SEM) with Partial Least Square (PLS). The population consisted of 493 students of Sekolah Menengah Kejuruan Harapan Bangsa, with a sample of 151 twelfth-grade students selected through purposive sampling. Research instruments included the school well-being scale, growth mindset scale, and grit scale. The results showed that school well-being had a positive and significant effect on grit (β = 0.392; t = 3.363; p = 0.001) and on growth mindset (β = 0.826; t = 19.770; p = 0.000). Furthermore, growth mindset had a positive and significant effect on grit (β = 0.496; t = 4.202; p = 0.000). Growth mindset also significantly mediated the relationship between school well-being and grit (t = 4.125; p = 0.000), with an indirect contribution of 41.0%. This study concludes that school well-being plays an important role in fostering grit both directly and indirectly through the development of a growth mindset.